MASKULINITAS DALAM L'MEN - Agung Budi Prasetyo (IKOM UMY, 2015)
This reseorch is trying to analyze about masculinities construction toward the L'A4EN advertisement. The purpose of this research is want to understand how the masculinities concept which constructed by L'IAEN through the several of advertisement concepts and how the society understand of that construction. The writer can conclude that most of the informants give the same view. It is called dominant hegemonic. From the result, we can understand that social class from the background of each informant is not relevance in the reception of masculinities concept when they read the messoge of L'IAEN advertisement.